Removing low-frequency artefacts from Datawell DWR-G4 wave buoy measurements - J.-V. Björkqvist (Geoscientific Instrumentation, Methods and Data Systems, 2016)
In this study we describe a previously unreported error in the vertical-displacement time series made with GPS-based Datawell DWR-G4 wave buoys and introduce a simple method to correct the resulting wave spectra. The artefact in the time series is found to resemble a sawtooth wave, which produces an erroneous trend following an f−2 power law in frequency space. The correction method quantifies the amount of erroneous trend below a certain maximum frequency and removes the spurious energy from all frequencies assuming the above-mentioned f−2 power law. The presented correction method is validated against an experimental field test, and its impact on the measured significant wave height is quantified. The method's sensitivity to the choice of the maximum frequency is also briefly discussed.